Edukasi Diet Rendah Garam dan Pembatasan Cairan terhadap Self Efficacy dan Motivasi untuk Sembuh pada Pasien Hemodialysis - Yulinawati, Yulinawati; Katmini, Katmini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine low salt diet education and fluid restriction on self-efficacy in controlling fluid salt intake and motivation to recover in haemodialysis patients. The method used in this research is quasi-experimental research. This quasi-experimental uses a Non Equivalent Control Group design or often called Non Randomised Control Group Pretest And Posttest Design. The results showed that based on the results of the Dependent T Test there was a difference in Self Efficacy before and after education in the intervention group with a p-value of 0.001 <0.05 with a t value of 4.661 there was a difference in motivation to recover before and after education in the intervention group with a p-value of 0.001 <0.05 with a t value of 4.001. The conclusion of this study is that low salt diet education and fluid restriction have an effect on Self Efficacy and motivation to recover in haemodialysis patients. Keywords: Education, Haemodialysis, Self Efficacy, Motivation